The Effectiveness of Public Procurement Processes and Their Role in Improving Public Demand and Rationalizing Public Expenditures: A Case Study of a Public Administrative Institution (2024) - Saim Tahar, Kihel Mohammed Reda, Hamidi Sihem Ikram, (European Economic Letters (EEL), 2024)
This study aims to analyze the various methods and techniques employed in public procurement processes, with a particular emphasis on the role of external oversight in enhancing the financial efficiency of public expenditures, in line with the provisions of Presidential Decree No. 15-247, dated September 16, 2015. It also focuses on the new provisions introduced by Law No. 23-12, enacted on August 5, 2023, which establishes the general rules governing public procurement. Economic operators provide their services with the dual objectives of generating profits and meeting the needs of public purchasers. Conversely, the contracting authority, as a public purchaser, seeks to achieve predefined objectives, including the successful execution of development projects, while adhering to the principle of optimal utilization of public funds and ensuring the efficiency of public procurement, which constitutes the core purpose of public contracts. Within this framework, an investigative study was conducted at a Public Administrative Establishment (Local administration directorate of the Oran province, 2024). The findings of the investigation highlight several observations, such as the need to strengthen efforts, particularly in the legal and regulatory domains, and to provide appropriate legislative frameworks for the various stages of the public procurement process. Furthermore, it is imperative to revise the current methods and techniques utilized in public procurement, as they are relatively slow and fail to align with the objectives envisioned by the contracting authority.